Intellectual Discourse and the Politics of Modernization: Negotiating Modernity in Iran by 'Ali Mrsepassi, Cambridge, New York: Cambridge University Press, 2000. xiv+ 193 pages. Notes top. 215. Bib{. to pages 223. lndex top. 227. (American Journal of Islam and Society, 2001)
This book examines the Islamic revolution of Iran and presents a culturalapproach to analyzing the events that resulted in the collapse of themonarchical system and the establishment of the Islamic Republic.The book contains seven chapters. An introductory chapter explores thegenealogy of the western narrative of modernity and its dichotomizingrepresentation of non-western cultures and societies. The author posesseveral questions in an attempt to provide a definition for modernity, and inthe process explores the story of Iranian modernity. Is modernity atotalizing ideology grounded in European cultural and moral experienceand incapable of understanding other cultures? Or, is it a mode of social andcultural experience of the present that is open to all forms of contemporaryexperiences and possibilities?These questions are addressed in chapter 1, where Mirsepassi examinesthe process of development of the concept of modernity in the West. Heanalyzes some of the writings of such thinkers as Montesquieu, Hegel, KarlMarx, Max Weber, Emmile Durkheim, Marshall Berman, JurgenHabermas, Anthony Giddens, and more recent works by critics ofmodernity theories such as Edward Sai'd, Arturo Escobar, and TimothyMitchell. He demonstrates quite convincingly, how in the westernconception of modernity, an "Oriental" other, passive, traditional, andirrational, is contrasted to the modem world of the West. At the depth of thediscourse of modernity, he finds a hostility to non-western cultures thatexcludes them from the possibility of meaningful participation in themaking of the modem world. He criticizes the western conception ofmodernity because it is Euro-centric and denies other cultures a positiverole in the making of the modem world. These theories all share the beliefthat "they are objective, culturally neutral, and universally applicable to allsocieties." (pp. 6-9) Therefore, the core conception of modernity theory ...